ANALISIS PELAKSANAAN PENILAIAN AUTENTIK KURIKULUM 2013 DI SEKOLAH DASAR - Ulah, Jumrotul; Galuh Kartika Dewi; Satrio Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the background of a paradigm shift in the implementation of the 2013 curriculum assessment. Assessment that is relevant to the preparation of the 2013 curriculum is authentic assessment. The purpose of this research is to describe the implementation of the 2013 curriculum authentic assessment on cognitive aspects as well as the inhibiting factors in the implementation of the 2013 curriculum authentic assessment in elementary schools. This research used qualitative method. The subjects of this research were grade III and grade VI teachers at SDN Mojorangagung. Data were collected through observation, interview, and documentation techniques. Data analysis used the Miles and Huberman analysis technique. The research results obtained show that teachers have carried out authentic assessment on cognitive aspects. The assessment process is carried out through four main stages consisting of assessment planning, carrying out assessment activities, analysing assessment results and follow-up, and reporting assessments. However, in its implementation there are inhibiting factors. Internal factors are class and time management and some students who are less cooperative in the implementation of the assessment. While external factors include never having participated in training, many assessment indicators that require a lot of time, inadequate facilities and infrastructure.